Domestic duck production : science and practice [ - Cherry, P. [ (Peter)] , 1937-; Morris, T. R. [ (Trevor Raymond)] (Wallingford, Oxfordshire : CABI, 2008)
Ducks are kept for profit in a great diversity of circumstances in both temperate and tropical climates. Outlining the biology of the domestic duck, this book provides quantitative descriptions of nutritional and environmental effects on growing and breding ducks, as well as practical advice on husbandry, housing and management.
1. History and biology of the domestic duck -- 2. Systems of production -- 3. Housing and environment -- 4. Husbandry of table duckling -- 5. Nutrition and factors affecting body composition -- 6. Rearing of parent stock -- 7. Management of breeding ducs -- 8. Fertility and hatchability -- 9. Genetic improvement
Includes bibliographical references and index
Keywords: Ducks